2014
DOI: 10.1016/j.biochi.2013.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Defining the impact on yeast ATP synthase of two pathogenic human mitochondrial DNA mutations, T9185C and T9191C

Abstract: Mutations in the human mitochondrial ATP6 gene encoding ATP synthase subunit a/6 (referred to as Atp6p in yeast) are at the base of neurodegenerative disorders like Neuropathy Ataxia Retinitis Pigmentosa (NARP), Leigh syndrome (LS), Charcot-Marie-Tooth (CMT), and ataxia telangiectasia. In previous studies, using the yeast Saccharomyces cerevisiae as a model we were able to better define how several of these mutations impact the ATP synthase.Here we report the construction of yeast models of two other ATP6 path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 45 publications
5
38
0
Order By: Relevance
“…Filter sterilized oligomycin (Sigma-Aldrich, St. Louis, MO, United States) was used as control treatment at the final concentration of 10 µg/mL, since it is known as a growth inhibitor of fungi, such as Aspergillus spp., Candida spp., and Penicillium spp. (Eliskases-Lechner and Prillinger, 1996), through inhibition of ATP synthase activity (Manfredi et al, 2002;Kabala et al, 2014) and mitochondrial respiration (Galloway et al, 2012;Kooragayala et al, 2015).…”
Section: Biological Material Growth Conditions and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Filter sterilized oligomycin (Sigma-Aldrich, St. Louis, MO, United States) was used as control treatment at the final concentration of 10 µg/mL, since it is known as a growth inhibitor of fungi, such as Aspergillus spp., Candida spp., and Penicillium spp. (Eliskases-Lechner and Prillinger, 1996), through inhibition of ATP synthase activity (Manfredi et al, 2002;Kabala et al, 2014) and mitochondrial respiration (Galloway et al, 2012;Kooragayala et al, 2015).…”
Section: Biological Material Growth Conditions and Treatmentsmentioning
confidence: 99%
“…Slight mitochondrial alterations, consisting of a less dense mitochondrial matrix with a sporadic occurrence of circular cristae, were found in P. cinnamomi only at 10 DAI (Figures 2O,P). The ATP synthase inhibitor oligomycin (Manfredi et al, 2002;Kabala et al, 2014), known to impair fungal growth (Eliskases-Lechner and Prillinger, 1996) and mitochondrial respiration (Galloway et al, 2012;Kooragayala et al, 2015), caused severe mitochondrial alterations in both P. infestans and P. cinnamomi already at 4 DAI and showed either the disappearance or profound rearrangement of the mitochondrial cristae ( Supplementary Figure S2). Taken together, these observations indicated that tagatose altered the mitochondrial structure of P. infestans with consequent inhibition of radial growth.…”
Section: Tagatose Differentially Inhibits Phytophthora Infestans and mentioning
confidence: 99%
“…Light and electron microscopic mitochondrial imaging was performed as described before (Jackson et al, 2014c;Schaller et al, 2011a). Skeletal muscle homogenates were prepared as described previously and the enzymatic activities of the respiratory chain complexes and the mitochondrial matrix marker enzyme citrate synthase were measured Jesina et al, 2004 Adapted from L opez-Gallardo et al 2014, Verny et al (2011), Kabala et al (2014), Jesina et al (2004), and Kogelnik et al, (1996). Mutations in MT-ATP6 (mtDNA NC_012920.1: nt.8527e9207).…”
Section: Biochemical and Microscopic Analysesmentioning
confidence: 99%
“…the 500-1500 member mitochondrial proteome is nuclearly encoded (Steinmetz et al 2002a;Sickmann et al 2003;Perocchi et al 2008;Rhee et al 2013). Thus, S. cerevisiae is an excellent model for studies of human mitochondrial and nuclear-mitochondrial gene product functions (Steinmetz et al 2002a;Schwimmer et al 2006;Perocchi et al 2008;Baile and Claypool 2013;Rutter and Hughes 2015), as well as for nuclear-mitochondrial pathogenic polymorphisms (Stumpf and Copeland 2011;Montanari et al 2013;Kabala et al 2014;Lodi et al 2015).…”
mentioning
confidence: 99%